2017
DOI: 10.1016/j.apsusc.2016.11.135
|View full text |Cite
|
Sign up to set email alerts
|

Growth and shape of indium islands on molybdenum at micro-roughened spots created by femtosecond laser pulses

Abstract: Indium islands on molybdenum coated glass can be grown in ordered arrays by surface structuring using a femtosecond laser. The effect of varying the molybdenum coated glass substrate temperature and the indium deposition rate on island areal density, volume and geometry is investigated and evaluated in a physical vapor deposition (PVD) process. The joined impact of growth conditions and spacing of the femtosecond laser structured spots on the arrangement and morphology of indium islands is demonstrated. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A metallic indium precursor was deposited by PVD onto Mo substrates, which were pre-structured by femtosecond laser pulses [47,48]. This site-selective modification of the Mo surface [49] promoted the localized deposition of In and thus created an easily tunable arrangement of nucleation sites [46][47][48], as schematized in figure 6(a). The In islands were subsequently coated by Cu and converted into CISe by a selenization process, after which excess Cu-Se was removed by a KCN etching step.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
“…A metallic indium precursor was deposited by PVD onto Mo substrates, which were pre-structured by femtosecond laser pulses [47,48]. This site-selective modification of the Mo surface [49] promoted the localized deposition of In and thus created an easily tunable arrangement of nucleation sites [46][47][48], as schematized in figure 6(a). The In islands were subsequently coated by Cu and converted into CISe by a selenization process, after which excess Cu-Se was removed by a KCN etching step.…”
Section: Bottom-up Approachesmentioning
confidence: 99%
“…At the same time, further island nucleation is suppressed in the vicinity of an existing island due to the constant depletion of freely diffusing indium. The radius around each island within which further nucleation is suppressed extends up to several hundred micrometers, depending on the experimental conditions [17]. The schematic process of indium island growth on molybdenum-covered glass substrates that were structured by a femtosecond (fs-)laser to induce nucleation at predefined locations is depicted in Fig.…”
Section: Reviewmentioning
confidence: 99%
“…The indium island size was adjusted by the indium deposition rate. Small islands (diameter: 40 µm) were obtained by a deposition rate of ~ 0.5 Å/s, large islands (diameter: 60 µm) resulted from a deposition at ~ 0.3 Å/s (for more details of optimizing the indium island self-assembled growth, refer to our previous work [13,14]). After cooling to room temperature, a copper layer of several hundred nanometer thickness was deposited at a nominal rate of 1 Å/s by PVD to obtain the desired indium-copper precursors (Figure 1b).…”
Section: Fabrication Of Micro-absorbersmentioning
confidence: 99%
“…Since the final micro cells must be aligned to a micro lens array, the indium precursor islands must be regularly arranged and exhibit a suitable morphology. In a previous publication we have recently demonstrated that indium islands as precursor material can be site-selectively grown on the back contact (a molybdenum layer deposited on glass) taking benefit of the fs-laser processing technology [13,14]. This allows to arrange the precursor material into a regular array matching the lateral dimensions of micro-lens arrays.…”
Section: Introductionmentioning
confidence: 99%